A historical study of the geography of the northeastern region of Iran and the approaches of the nation-state to the Akhal contract - alireza mohajeri; reza shaabani; sina foroozesh (تحقیقات کاربردی علوم جغرافیایی)
The Qajar period should be considered as a period of numerous economic, political, and military treaties, treaties, and treaties. Territorial, trade, and economic expansionism imposed on Iran by the clever politicians of foreign governments with superior military power, and many benefits from these treaties and agreements benefited these countries, especially Russia. Following that, geographical and historical developments began in the Turkmen settlements of northeastern Iran. This article has been prepared with the aim of analyzing the historical geography of Khorasan region in the northeast and the approach of the government-nation of Iran to the Akhal contract. It is a descriptive-analytical research method. Research data is collected through documentation and library. The analysis of the article has been done with a qualitative approach based on documents and arguments. The analytical results showed geographical and border changes in the northern part of Iran. As part of the Akhal contract, parts of northeastern Iran were annexed to Russia and Iran's historical geography in northeastern socio-political changes and the reaction of the Turkmen people while the photo There was no action among Qajar government officials.